Decoupling and shielding numerical optimization of MRI phased-array coils. (March 2016) - Hartwig, V.; Vivoli, G.; Tassano, S.; Carrozzi, A.; Giovannetti, G.
Abstract: Receiver array coils in magnetic resonance imaging systems are used to pick up the signals emitted by the nuclei with high signal-to-noise ratio and a large region of sensitivity. Especially in low-field magnetic resonance systems, receiver coil performance plays a significant role in image quality. Moreover, since the magnetic resonance scanner shielding system strongly modifies resonance frequencies and field distribution, the array coils performance should be evaluated in dependence on the shield position. In this paper, we describe the use of a numerical solver based on finite-difference time-domain method to evaluate coil performances also considering the presence of radiofrequency shields. In particular, this paper deals with coupling and shielding in phased array coils at low field: we analyzed a classic two circular elements array and a novel two elements array coil both designed for the application in a 0.5 T open magnetic resonance scanner. The prototypes of the arrays were tested by laboratory workbench in order to validate the simulated data and experiments were also done in real low field magnetic resonance scanner by using the novel coil.